2014
DOI: 10.1002/cbic.201402166
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Enzymatic Degradation of Oxidized Polyvinyl Alcohol

Abstract: The ever-increasing production and use of polyvinyl alcohol (PVA) threaten our environment. Yet PVA can be assimilated by microbes in two steps: oxidation and cleavage. Here we report novel α/β-hydrolase structures of oxidized PVA hydrolase (OPH) from two known PVA-degrading organisms, Sphingopyxis sp. 113P3 and Pseudomonas sp. VM15C, including complexes with substrate analogues, acetylacetone and caprylate. The active site is covered by a lid-like β-ribbon. Unlike other esterase and amidase, OPH is unique in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Additionally, regardless of changes in the concentration of G-L-PRF, the breaking elongation ratio remained around 300%, and no cytotoxicity was observed. Therefore, our results suggested that G-L-PRF may have an effect on PVA internal termolecular crosslinks and morphology 38 , 39 . The morphology of G-L-PRF/PVA scaffolds changed at different concentrations, demonstrating that G-L-PRF affected PVA crosslinks.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, regardless of changes in the concentration of G-L-PRF, the breaking elongation ratio remained around 300%, and no cytotoxicity was observed. Therefore, our results suggested that G-L-PRF may have an effect on PVA internal termolecular crosslinks and morphology 38 , 39 . The morphology of G-L-PRF/PVA scaffolds changed at different concentrations, demonstrating that G-L-PRF affected PVA crosslinks.…”
Section: Discussionmentioning
confidence: 62%
“…Iterative oxidation and further degradation by aldolase and β-diketone hydrolyase along the PVA backbone lead to simple byproducts, such as acetic acid. Image adapted with permission from refs ( 10 ) and ( 11 ). Copyright 2008 Woodhead Publishing and 2014 Wiley.…”
Section: Common Chemistries Used For Biodegradable Materialsmentioning
confidence: 99%
“…[ 11,22–26 ] In natural environments, PVA can be fully degraded into CO 2 and H 2 O by microorganisms through the oxidation of PVA hydroxyl groups into diketones and the subsequent hydrolysis of carbon–carbon diketone bonds. [ 11,22,27,28 ] Therefore, PVA‐based plastics are environmentally friendly and degradable, and they can be used for a wide range of potential applications. [ 29,30 ] PVA‐based plastics have been fabricated by complexation of PVA with partner species such as inorganic nanofillers, [ 31 ] organic molecules, [ 32 ] and polymers [ 25,30 ] containing complementary noncovalent interactions.…”
Section: Figurementioning
confidence: 99%
“…Further, the microorganisms in the soil adhered to plastic surfaces and secreted enzymes such as dehydrogenase, oxidase, hydrolase, and aldolase. [22,27,28] Vanillin can hydrolyze from VPVA chains through catalysis of Lewis acids such as Fe 3+ , Ca 2+ , and Al 3+ ions in soil. [51,52] Dehydrogenase and oxidase can oxidize the aliphatic hydroxyl groups of PVA to diketone groups, while hydrolase and aldolase can catalyze the cleavage of the carboncarbon bonds of diketones.…”
mentioning
confidence: 99%